Obtaining vegetable dyes as a didactic resource in Biology laboratories - Pozo-Zapata, Raúl (2024)
Natural dyes are millenary discoveries that have been used since ancient Greece to color numerous objects such as sculptures but have lost their usefulness and have been replaced by artificial dyes that can be harmful to health. The purpose of this study is to obtain a natural vegetable dye from the hibiscus flower using vinegar as a solvent, to be used as a didactic resource in the experimental practices of the biology laboratory. The hypothesis of the study indicates that a useful colorant can be obtained from the calyxes of the hibiscus flower, demonstrating its function in the experimental observations in the practices of mitosis and meiosis. The method used was descriptive and observational since experimental activities were carried out applying the reagent and dye obtained. The dyes and reagents required for such practices are of high cost and those obtained as a result of this research were of low cost, the acetic orcein in the market has a value of $31.3 for 60 ml, while in the research carried out the cost of the pigment was $0.76 for 60 ml and the reagent that replaced the hydrochloric acid that in the market costs $6 for 500 ml, the reagent obtained had a value of $2.36 for 500 ml; the products obtained had a similar performance to those acquired in the industry. The results contribute with resources that will allow for better.